Biological Characteristics and Genetic Analysis of a Highly Pathogenic Proteus Mirabilis Strain Isolated From Dogs in China - Hu, Renge; Wang, Xue; Muhamamd, Inam; Wang, Yiming; Dong, Wenlong; Zhang, Haipeng; Wang, Yu; Liu, Shuming; Gao, Yunhang; Kong, Lingcong; Ma, Hongxia (Frontiers in Veterinary Science, 2020)
To evaluate the antimicrobial resistance and virulence gene characteristics of highly pathogenic Proteus mirabilis (P. mirabilis). In this study, we isolated P. mirabilis CC15031 from diarrhea dogs in China, tested the median lethal dose (LD50) and measured the minimum inhibitory concentration (MIC) of 10 different antibiotics commonly used in veterinary clinic. Meanwhile presented the complete genome sequence annotations to analyze the virulence and resistance formation mechanism. The results showed that the CC15031 presented a relatively potent pathogenicity in mice (LD50=0.57×106 CFU) and exhibited a highly degrees of resistance to all the tested antimicrobial agents. The CC15031 genome of 4,031,742 bp with 3745 predicted genes had an average gene length of 917 bp and 38.99% GC content. A new variant of integrative and conjugative eliement (ICE) with type IV secretion system (T4SS) (217,446bp) conferring multidrug resistance was identified and characterized by structural analysis in CC15031. These data provide a foundation for understanding the genomic features and antimicrobial resistance mechanisms of this pathogen.